Prevalence of Kudoa thyrsites (Myxozoa, Multivalvulida) in Atlantic Mackerel, Scomber scombrus L., in the Vicinity of the Faroe Islands - Højgaard, Dánjal Petur; í Homrum, Eydna; Salter, Ian (Frontiers in Marine Science, 2022)
Atlantic mackerel Scomber scombrus is an important migratory fish in Faroese waters and the Northeast Atlantic at large. Similar to other fish species from marine environments, mackerel can be infected by the myxozoan parasite Kudoa thyrsites, leading to myoliquefaction that renders the fish commercially unviable. Despite the ecological and economic significance of K. thyrsites as a parasite, little is known regarding its prevalence in the Faroese mackerel fishery. Prior to analysing field samples, we examined 104 samples of Atlantic mackerel selected from a Faroese processing plant on the basis of visible soft-tissue. Using microscope smears we observed K. thyrsites in 98% of the soft-tissue mackerel specimens and a direct comparison with qPCR demonstrated strong agreement between the two techniques (Φ = 0.429, p<0.01; Fisher’s exact test). We used qPCR to analyze a total of 594 Atlantic mackerel specimens, collected from Faroese fishing grounds during 2017 and 2018. Overall prevalence was 4.1% (95% confidence interval; 2.5-5.7%) and ranged from 0-14% at different locations. Infection by K. thyrsites was documented in fish as young as 2 years (195g) and up to 14 years (615g) of age. A logistic regression model indicated the odds of infection were statistically associated with sampling location and month, but not gender, age, weight or length, although a Chi-squared test on age categories showed the oldest fish (>10 years) had highest prevalence (10.8%, CI: 4.2-17.5%). In order to investigate potential infection pathways we performed qPCR analysis on eDNA in water samples collected from the Faroese Plateau. However, we found no molecular evidence for K. thyrsites spores in Faroese plankton assemblages. Our data support the prevailing hypothesis that both the alternating invertebrate host and infection of Atlantic mackerel by K. thyrsites occurs in more southern waters.